Survey of Ocular Trauma at Groote Schuur Hospital in Cape Town, South Africa - Logday, Zahra (Division of General Surgery, 2024)
Background. Ocular trauma is an important cause of unilateral blindness around the world. There have been a few studies around South Africa that demonstrate the causality and outcomes, however, to date, no single study has been done that represents all ocular trauma cases that present to the trauma unit of Groote Schuur Hospital in Cape Town, South Africa. Objectives. To investigate the epidemiology of ocular trauma cases that present to Groote Schuur Hospital in Cape Town, South Africa from 1 December 2019 to 31 May 2020. Methods. This was a retrospective cohort study of all ocular trauma cases seen at C14 Trauma Unit of Groote Schuur Hospital over a 6-month period. Results. There was a total of 1301 trauma cases that presented to C14 and a total of 47 ocular trauma cases, representing 3.6% of total trauma cases. Assault was the most common manner of trauma. Most cases involved males and those aged 18-30. Most cases were referred from primary healthcare facilities and 47% of cases required medical management only. During COVID-19, there was a significant decline in the number of ocular trauma cases. Conclusion. Assault is the most common cause of ocular trauma and is preventable. Many cases can be managed at a primary level of health care by upskilling peripheral health centers in ocular trauma. Active engagement is needed on a multisystem level to mitigate the general level of violence.